2016
DOI: 10.1255/ejms.1440
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Hydrocarbon Bidentate Bonding in Alkyl Acetates, Methyl Alkanoates, Alcohols and 1-Alkenes: A Comparative Study

Abstract: The relative affinity of the monovalent metal ions Li, Na, Cu and Ag towards a series of aliphatic alkyl acetates and some selected 1-alkenes (P) was examined using the kinetic method. A detailed analysis of the dissociation characteristics of a series of mixed metal-bound dimer ions of the type P-M-P and the evaluated proton affinities (PAs) of the monomers shows that the affinity of the cation towards long-chain alkyl acetates and alkenes (having a chain length ≤ C) is markedly enhanced. In line with recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In a preliminary experiment we generated the proton bound dimer [CD 3 C(=O)OH]•••H + •••[HC(=O)OCH 3 ] and observed that it dissociated to m/z 64 ([CD 3 C(OH) 2 ] + ) and to m/z 61 ([HC(OH)OCH 3 ] + ) in a ratio of 2.12 ± 0.20. It has been established that in such kinetic method experiments for these classes of compounds, the equation ΔPA (kJ/mol) = 2lnR holds, 16 18 where R is the ratio of the product ions, in this case 2.12. This leads to a difference in PAs of acetic acid and methyl formate of only 1.5 ± 0.4 kJ/mol and so the PAs of acetic acid and methyl formate are indeed closely similar.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a preliminary experiment we generated the proton bound dimer [CD 3 C(=O)OH]•••H + •••[HC(=O)OCH 3 ] and observed that it dissociated to m/z 64 ([CD 3 C(OH) 2 ] + ) and to m/z 61 ([HC(OH)OCH 3 ] + ) in a ratio of 2.12 ± 0.20. It has been established that in such kinetic method experiments for these classes of compounds, the equation ΔPA (kJ/mol) = 2lnR holds, 16 18 where R is the ratio of the product ions, in this case 2.12. This leads to a difference in PAs of acetic acid and methyl formate of only 1.5 ± 0.4 kJ/mol and so the PAs of acetic acid and methyl formate are indeed closely similar.…”
Section: Resultsmentioning
confidence: 99%
“…butyl acetate]•••Na + •••[iso propyl acetate] using the lnR versus PA curves for the proton bound and sodium bound dimers as references. 17 , 18 Since the slope of the lnR versus PA curve for the sodium bound dimers is only ¼ of the slope of the lnR versus PA curve for the proton bound dimers, 16 18 the experimental error for the derived PA of tert butyl acetate is concomitantly larger, see Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations